IMPLEMENTASI STRATEGI PEMBELAJARAN PAI DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN SISWA SLB KUTAI KARTANEGARA - Cahyani, Maulida Argia; Maryam; Fathimadani, Annisa; Aalma, Alya Desvita; Miansi, Aalsabila Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of Islamic Religious Education (PAI) learning strategies in improving the religious understanding of students with special needs at SLB Kutai Kartanegara. This research uses a qualitative descriptive approach to obtain an in-depth understanding of the learning process, student characteristics, and factors influencing learning effectiveness. Data were collected through observation, interviews, and documentation involving teachers, school principals, students, and parents. The results show that the implementation of PAI learning strategies is carried out adaptively by considering the diverse abilities and needs of students. Learning emphasizes not only cognitive aspects but also affective and psychomotor aspects through habituation, direct practice, repetition methods, and the use of visual media. Various strategies such as expository, demonstration, discussion, and individualized learning have proven effective in improving students' religious understanding. However, there are several challenges, including limited facilities and varying student conditions. The role of teachers is crucial as facilitators, mentors, and role models in creating meaningful and flexible learning. Therefore, the success of PAI learning in special schools is highly dependent on the teacher’s ability to adapt strategies to student characteristics and the support of the surrounding environment.